Learning Stimulus‐Location Associations in 8‐ and 11‐Month‐Old Infants: Multimodal Versus Unimodal Information. (16th July 2014) - ter Schure, Sophie; Mandell, Dorothy J.; Escudero, Paola; Raijmakers, Maartje E. J.; Johnson, Scott P.
<x xml:space="preserve">Abstract</x> Research on the influence of multimodal information on infants' learning is inconclusive. While one line of research finds that multimodal input has a negative effect on learning, another finds positive effects. The present study aims to shed some new light on this discussion by studying the influence of multimodal information and accompanying stimulus complexity on the learning process. We assessed the influence of multimodal input on the trial‐by‐trial learning of 8‐ and 11‐month‐old infants. Using an anticipatory eye movement paradigm, we measured how infants learn to anticipate the correct stimulus–location associations when exposed to visual‐only, auditory‐only (unimodal), or auditory and visual (multimodal) information. Our results show that infants in both the multimodal and visual‐only conditions learned the stimulus–location associations. Although infants in the visual‐only condition appeared to learn in fewer trials, infants in the multimodal condition showed better anticipating behavior: as a group, they had a higher chance of anticipating correctly on more consecutive trials than infants in the visual‐only condition. These findings suggest that effects of multimodal information on infant learning operate chiefly through effects on infants' attention.